Manual therapy and therapeutic exercise in the treatment of osteoarthritis of the hip: a systematic review - A. Romeo; S. Parazza; M. Boschi; T. Nava; C. Vanti (PAGEPress Publications, 2013)
This systematic review aimed at investigating the role of therapeutic exercise and/or manual therapy in the treatment of hip osteoarthritis (OA). Two independent reviewers (AR, CV) searched PubMed, Cinahl, Cochrane Library, PEDro and Scopus databases and a third one (SP) was consulted in case of disagreement. The research criteria were publication period (from May 2007 to April 2012) and publication language (English or Italian). Ten randomized controlled trials matched inclusion criteria, eight of which concerning therapeutic exercise and two manual therapy. Few good quality studies were found. At mid- and long-term follow-up land-based exercises showed insufficient evidence of effectiveness with respect to pain and quality of life, but positive results were found for physical function. Water exercises significantly reduced fall risk when combined with functional exercises. Programs containing progressive and gradual exposure of difficult activities, education and exercises promoted better outcomes, higher adherence to home program and increased amount of physical activity, especially walking. Manual therapy seemed to reduce pain and decrease disability at short-term. Less use of nonsteroidal anti-inflammatory drugs was statistically significant at long-term follow-up in patients treated with manual therapy. The relationship between clinical results and radiological grade of OA was not investigated. Encouraging results were found in recent literature for manual therapy and functional training. Further research is needed to elucidate this issue through high-quality trials, especially addressing the aspects that have not been thoroughly explored yet, for instance type, amount and scheduling of conservative treatment.